Pengaruh Penggunaan Media Digital Berbasis Video Youtube Terhadap Hasil Belajar Siswa Kelas IV SD pada Materi Perubahan Wujud Benda - Putri, Rika Hayani; Ismail, Ali; Panjaitan, Regina Lichteria (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of using digital learning media based on YouTube videos on the learning outcomes of fourth-grade elementary school students in the topic of changes in the states of matter. The research employed a quasi experimental method with a nonequivalent control group design. The sample consisted of two classes; the experimental class received instruction through YouTube videos, while the control class used the traditional lecture method. Data we collected using pretest and posttest to asses cognitive learning outcomes, and questionnaires were distributed to measure learning student responses toward the learning media. The results showed a significant improvement in the experimental class average score, increasing from 52,17 to 78,29, compared to the control class which rose from 55,33 to 63,50. The Mann-Whitey test revealed a significance value of 0.003 (p<0,05), indicating a significant difference between the groups. Furthermore, student responses to the use of YouTube video media were highly positive, whit an average response rate of 95,05%. These findings indicate that YouTube-based digital learning media is effective alternative in teaching, especially for topics requiring concrete visualization such as changes int the states of matter.